Characteristics of Tumor Marker on Mediastinal Tumors - Novpiodita Pratiwi; Setia Putra Tarigan; Novi Novisari Soeroso; Putri Chairani Eyanoer (Indonesian Health Journal, 2026)
Mediastinal tumors are rare thoracic malignancies that pose diagnostic and therapeutic challenges due to their anatomical proximity to vital organs and diverse histopathological features. Early detection and accurate characterization are essential for effective management. This study aimed to describe the characteristics of tumor markers and their diagnostic relevance in patients with mediastinal tumors treated at Adam Malik General Hospital, Medan, Indonesia. A descriptive observational study using a case series design was conducted on 43 patients diagnosed with histopathologically confirmed mediastinal tumors from 2020 to 2024. Data on demographics, tumor histopathology, tumor location, and tumor marker levels (LDH, AFP, B-HCG, and CEA) were collected from medical records. Statistical analysis was performed using SPSS 26.0, with categorical variables expressed as frequencies and percentages, and numerical variables as mean ± standard deviation. The results indicated that the majority of patients were male (76.7%), with a mean age of 40.7 ± 15.5 years. Lymphoma (39.5%) and thymoma (37.2%) were the most common tumor types, predominantly located in the anterior mediastinum (76.7%). LDH was elevated in 76.7% of cases, particularly in germ cell tumors and lymphomas, while AFP and B-HCG elevations were mainly observed in germ cell tumors. CEA had limited diagnostic utility. The study concludes that integrating clinical, histopathological, and tumor marker data enhances diagnostic accuracy, and that LDH, AFP, and B-HCG serve as valuable supportive biomarkers for mediastinal tumor evaluation.